Design and development of single-axis solar tracking system and water level control for application of line focus concentrator for solar desalination process - Muhammad Adam, Zahari (2017)
The lack of drinking water has been a great challenge for humanity which continues to the present and will continue in the future. One of the solutions to solve this problem is solar desalination technology. The thermal conversion of solar concentrators makes it possible to reach high temperatures able to boil the salted water with pressures higher or equal to the atmospheric one. Thus, for increases the efficiency of solar desalination plant, the solar tracking system was designed to make the system more flexible to trap the sunlight. The main mechanism of the solar tracking system consists of the tracking device, tracking algorithm, control unit, positioning system, driving mechanism and sensing devices. The tracking algorithm determines the angles which are used to determine the position of solar tracker. This project discusses the design and construction of a prototype for solar tracking system that has a single axis of freedom. The control circuit is based on an ATMega328P microcontroller. It was programmed to detect sunlight via the LDRs before actuating the motor to position the parabolic frame. The parabolic frame is positioned where it is able to receive maximum light. By using this method, the application of line focus concentrator for solar desalination process will be more functional and get higher output of fresh water. Besides that, to make the system more flexible, we add the sensor which is ultrasonic sensor for measure water level. Therefore, we can make the process of desalination work automatically. The basic mechanisms of measure level sensor are controlled by using Arduino, solenoid valve, ultrasonic sensor and water pump. The control circuit is based on an Arduino microcontroller and was programmed to control the water flow into absorber tube. When the water reach at maximum point, the ultrasonic sensor will send the signal to solenoid valve to stop the water from flow into absorber tube. From the result, the highest amount of fresh water produces was 25ml when the average value of solar irradiance 318.00W/m2. Thus, it is found that the productivity of fresh water increases as the solar irradiation increases because the rate of evaporation depends on solar intensity and the weather. Besides that, when the bad weather occur during experimental, the solar tracking system will not performed well.